Perencanaan Usaha (Business Plan) - Hanifa Turrahmah (LPPM Universitas Multi Data Palembang, 2023)
The ability to incorporate innovative, creative, and bright ideas—as well as ideas with high economicand commercial value—into a mature and realistic business plan is one of the keys to business startupsuccess.whatever kind of company we’ll run.This is even more true if you follow up by writing down these ideas sothat they can be shared with other parties.Plans for what a business will do in the future include how to allocateresources, pay attention to important factors, and deal with problems and opportunities.A business plan generallyincludes the Summary, Mission Statement, Key Factors, Market Analysis, Production, Management, and FinancialAnalysis, including Break Event analysis, among other things.If we are going to run a business, a business plan isabsolutely necessary because it serves as a business’s equivalent of a map and compass.We can identify our primarybusiness objectives, prioritize tasks, and estimate cash flow with the help of a plan.In the meantime, if we have asound business plan, our chances of success will be higher.The process of good business planning is more than justa plan.Examples of good business planning are:easy to use (with features that are both practical andconvenient);Specific (specific in terms of time, personnel, and budget);Complete (complete with all components)and Realistic (in terms of goals, budget, and time targets).